Exploring the Impact of Green Marketing, Brand Image, and Purchase Intent on Consumer Decisions for Bogasari Flour Products - Yoki Muchsam; Galih Raspati; Yuyun Yuniati Yuningsih; Fitrah Rumaisa (International Journal of Multidisciplinary Sciences and Arts, 2025)
This research addresses the decline in consumer purchasing decisions for PT Indofood Sukses Makmur Tbk. and Bogasari Flour Mills, emphasizing the growing importance of green marketing in shaping consumer preferences for environmentally friendly products. The study aims to evaluate the influence of green marketing, brand image, and purchase intention on consumer purchasing decisions. Employing a descriptive associative method, the research utilizes a questionnaire distributed to 300 respondents selected through purposive sampling. Data analysis is conducted using SPSS 24, focusing on validity, reliability, correlation analysis, coefficient of determination, and multiple regression. The findings reveal a positive and significant impact of green marketing, brand image, and purchase intention on the sales of Bogasari flour by PT Indofood Sukses Makmur Tbk., indicating that these factors are crucial in influencing consumer purchasing decisions. The results suggest that companies should prioritize green marketing strategies and enhance their brand image to align with consumer preferences, ultimately improving sales performance in a competitive market. In conclusion, integrating green marketing, brand image, and purchase intention into sales strategies is essential for effectively influencing consumer purchasing decisions, enabling companies like PT Indofood Sukses Makmur Tbk. to navigate market challenges and seize growth opportunities.